2021
DOI: 10.1177/1527476420982230
|View full text |Cite
|
Sign up to set email alerts
|

Racism, Hate Speech, and Social Media: A Systematic Review and Critique

Abstract: Departing from Jessie Daniels’s 2013 review of scholarship on race and racism online, this article maps and discusses recent developments in the study of racism and hate speech in the subfield of social media research. Systematically examining 104 articles, we address three research questions: Which geographical contexts, platforms, and methods do researchers engage with in studies of racism and hate speech on social media? To what extent does scholarship draw on critical race perspectives to interrogate how s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(117 citation statements)
references
References 75 publications
(115 reference statements)
2
108
0
7
Order By: Relevance
“…Social media activities may also contribute to the polarization of political debates and stoke incivility in the public sphere (Stella et al, 2018;Theocharis et al, 2016). They have demonstrably enabled hate speech, harassment, and trolling, especially oriented toward women and minorities too (Matamoros-Fernández & Farkas, 2021;Sobieraj, 2020;Stecklow, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media activities may also contribute to the polarization of political debates and stoke incivility in the public sphere (Stella et al, 2018;Theocharis et al, 2016). They have demonstrably enabled hate speech, harassment, and trolling, especially oriented toward women and minorities too (Matamoros-Fernández & Farkas, 2021;Sobieraj, 2020;Stecklow, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hate speech detection is usually addressed as a supervised classification problem, where models are trained to distinguish between examples of hate and normal speech. A systematic literature review of academic articles on hate speech on social media, between 2014 and 2018 (Matamoros-Fernández and Farkas 2021 ), found that research was limited to text-based analyses of racist hate speech, to the Twitter platform, and to the content mostly from the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Data samples are collected from various sources on the Web (Table 3). Twitter is used in majority due to its popularity and the easiness to get data, while other social media (Formspring, YouTube, MySpace, Wikipedia, and Facebook) are used less [167]. Various sites such as the news website Gazzetta.it [198] usually specialized in one topic such as sport or politics and discussion forums such as voat, 4chan, or reddit are also investigated.…”
Section: Data Retrievalmentioning
confidence: 99%